Scale structure coating based on PDMS (Polydimethylsiloxane) / Co-coated SiO2 composite material as well as preparation method and application of scale structure coating

By modifying SiO2 nanoparticles on the surface of cobalt nanoparticles, a flake-structured coating of PDMS/Co@SiO2 composite material is constructed. Combining magnetic response and photothermal properties, the problem of low energy efficiency and poor adaptability of traditional anti-icing materials under extreme weather conditions is solved, and efficient directional transport of droplets and long-term stable anti-icing effect are achieved.

CN120795796APending Publication Date: 2025-10-17CIVIL AVIATION FLIGHT UNIV OF CHINA
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202511167752.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-20
Publication Date
2025-10-17

AI Technical Summary

Technical Problem

Traditional anti-icing materials have low anti-icing efficiency and poor environmental adaptability under extreme weather conditions, and cannot meet the high-performance material requirements of modern aviation.

Method used

By using PDMS/Co@SiO2 composite material, SiO2 nanoparticles are modified in situ on the surface of cobalt nanoparticles to construct a multi-level micro-nano structure coating. Combining magnetic response and photothermal anti-icing functions, micron-sized Co powder and PDMS are used to form a scale array to enhance superhydrophobicity and magnetic responsiveness. Efficient directional transport of droplets is achieved by applying an external magnetic field.

Benefits of technology

It effectively prevents water droplets from freezing in low-temperature environments, enables efficient directional transport of droplets, significantly improves anti-icing performance, and is suitable for aviation and power equipment fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120795796A_ABST
    Figure CN120795796A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of composite functional materials, in particular to a scale structure coating based on a PDMS / Co (at) SiO2 composite material and a preparation method and application of the scale structure coating. The preparation method comprises the following steps: mixing vinyl-terminated polydimethylsiloxane with methylhydrosiloxane to obtain a pre-polymerized solution; dispersing cobalt powder in the prepolymerization liquid to obtain a PDMS / Co mixture, coating the PDMS / Co mixture on the surface of a mold with a scale structure, and stripping the mold after curing to obtain a PDMS / Co scale array; and modifying SiO2 nanoparticles on the surface of the PDMS / Co scale array to obtain the scale structure coating based on the PDMS / Co coated SiO2 composite material. According to the invention, by constructing the multistage micro-nano structure and cooperating with the magnetic response and photothermal effect, a ''magnetostrictive unbalance-elastic rebound'' liquid drop directional transport mechanism and a photothermal-super-hydrophobic cooperative anti-icing function are constructed, and the problems of low energy efficiency, poor environmental adaptability and easy failure under extreme conditions of an existing anti-icing material are solved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of composite functional material preparation, in particular to a scale structure coating based on PDMS / Co@SiO2 composite material, a preparation method and application thereof. BACKGROUND

[0002] In recent years, the frequent occurrence of extreme weather has prompted the research of anti-icing technology to become the core topic in multiple fields. Especially in the field of aviation, the key components of landing gear face serious icing threats in low-temperature environments. Icing not only affects flight safety, but also causes equipment failure, resulting in catastrophic consequences. Although traditional anti-icing materials can play a role, they cannot effectively meet the demand for high-performance materials in modern technology due to their low anti-icing efficiency and poor environmental adaptability. SUMMARY

[0003] To overcome the defects of the prior art anti-icing materials, the present application provides a scale structure coating based on PDMS / Co@SiO2 composite material, a preparation method and application thereof. The present application designs a coating combining magnetic response and photothermal anti-icing functions based on PDMS / Co@SiO2 composite material. By compounding cobalt nanoparticles with a vinyl-terminated polydimethylsiloxane matrix and in-situ modifying SiO2 nanoparticles on the surface of cobalt nanoparticles, a composite system with multi-level micro-nano structure is successfully constructed. This unique structural design endows the scale structure coating based on PDMS / Co@SiO2 composite material with good superhydrophobicity, photothermal performance and magnetic response characteristics, enabling it to effectively prevent water droplets from icing at a low temperature of-15℃. Under the action of an external magnetic field, the coating can achieve efficient directional transportation of liquid droplets, effectively improving the anti-icing performance and enabling stable operation for a long time in extreme environments, providing a new anti-icing solution for the aviation and power equipment fields.

[0004] To achieve the above-mentioned purposes, the technical solution adopted by the present application is as follows: The first object of the present application is to provide a preparation method of a scale structure coating based on PDMS / Co@SiO2 composite material, comprising the following steps: S1. Using vinyl-terminated polydimethylsiloxane as a matrix and methylhydrogen siloxane as a curing agent, mixing the matrix and the curing agent to obtain a prepolymer solution.

[0005] S2. Dispersing cobalt powder in the prepolymer solution, and after degassing, obtaining a PDMS / Co mixture. The degassing is to eliminate bubbles to avoid shear thinning effect, ensure the density and stability of the scale structure coating based on PDMS / Co@SiO2 composite material, and reduce defects caused by bubble escape.

[0006] S3, coating the PDMS / Co mixture on the mold surface with scale structure, ensuring sufficient penetration into the microstructure of the mold, after curing treatment, peeling off the mold, during the curing process, the addition reaction of the vinyl group of polydimethylsiloxane and the methyl hydrogen siloxane occurs, forming a cross-linked three-dimensional network; at the same time, the cobalt powder particles are embedded into the cross-linked three-dimensional network, forming a stable composite structure, obtaining the PDMS / Co scale array.

[0007] The curing system of the vinyl-terminated polydimethylsiloxane used herein belongs to an addition type cross-linking mechanism, and the main reaction mechanism is as follows: the double bond (-CH=CH2) in the molecular chain of the vinyl-terminated polydimethylsiloxane reacts with the Si-H bond in the curing agent to form a Si-CH2-CH2-Si bond, thereby constructing a three-dimensional cross-linked network structure, so as to realize the transformation of the PDMS / Co mixture from a liquid state to an elastic solid state.

[0008] The mold surface with scale morphology presents a scale-like ordered arrangement, and this unique structure can manufacture a multi-level roughness feature, thereby effectively enhancing the super-hydrophobic performance of the scale structure coating based on the PDMS / Co@SiO2 composite material; at the same time, due to the flexible nature of the scale structure, when driven by a magnetic field, the scale structure will undergo buckling deformation, and after the magnetic field effect is eliminated, it will realize recovery deformation.

[0009] S5, modifying the SiO2 nanoparticles on the surface of the PDMS / Co scale array, further enhancing the roughness and hydrophobicity of the scale structure coating based on the PDMS / Co@SiO2 composite material, obtaining the scale structure coating based on the PDMS / Co@SiO2 composite material.

[0010] Preferably, the mass ratio of the vinyl-terminated polydimethylsiloxane to the methyl hydrogen siloxane is 8-12:1, more preferably 10:1. When the mass ratio of the vinyl-terminated polydimethylsiloxane to the methyl hydrogen siloxane is less than 8:1 (i.e., the proportion of the curing agent is too high), the cross-linking reaction rate is too fast, which will cause the viscosity of the prepolymer liquid to change too quickly during the coating process, making it difficult to form a uniform film; the scale structure replication is incomplete, the surface is rough; the film forming stress is too large, the flexibility decreases, and the prepolymer liquid becomes brittle; it is easy to break or difficult to demold when peeled off; when the mass ratio of the vinyl-terminated polydimethylsiloxane to the methyl hydrogen siloxane is higher than 12:1 (i.e., the proportion of the curing agent is too low), the cross-linking reaction is not sufficient, which will cause the curing time to be significantly prolonged; the cross-linking density is insufficient, the mechanical strength decreases; the flexibility is enhanced but the adhesion remains, which is easy to adsorb impurities; the prepolymer liquid is prone to adhesion, deformation, and even swelling during use; the Co in the PDMS / Co mixture is unevenly distributed, making the photo-thermal response and magnetic response performance unstable.

[0011] Preferably, the mass ratio of the cobalt powder to the prepolymer liquid is 0.2-0.3:1.

[0012] Preferably, the curing treatment is at 60-100℃ for 1-3h; more preferably, the curing treatment is at 80℃ for 2h. The cross-linking reaction of the vinyl-terminated polydimethylsiloxane is an addition type silicone rubber, which can be accelerated above 60℃; above 100℃, it can cause more volatilization, stress concentration or agglomeration of nanoparticles, thereby reducing the structural integrity; less than 1h, the reaction is incomplete, resulting in flake peeling or mechanical property degradation; more than 3h, the cross-linking is complete, and further extension does not significantly improve the performance, but increases the energy consumption.

[0013] Preferably, the mold with a scale structure is prepared by cutting the surface of a polyvinyl chloride plate to form a scale structure.

[0014] Preferably, the mold with a scale structure is also subjected to surface treatment, and the surface treatment operation is as follows: First, the scale structure surface is subjected to oxygen plasma cleaning, and then fluorosilane is deposited on the cleaned scale structure surface by vapor deposition to obtain a mold with a scale structure. The oxygen plasma cleaning serves to remove cutting residues and activate the surface of the scale structure template; the deposition of fluorosilane is to construct a low surface energy layer to improve the demolding effect.

[0015] Preferably, SiO2 nanoparticles are modified on the surface of the PDMS / Co scale array by a solution method or a vapor deposition method. The specific operation of modifying SiO2 nanoparticles by the solution method is as follows:

[0016] SiO2 nanoparticles (usually hydrophobic or surface active treated) are dispersed in anhydrous ethanol or deionized water, and after ultrasonic treatment for 30-60min, a suspension is obtained; the suspension is coated on the surface of the PDMS / Co scale array, and cured at 60-80℃ for 2-2.5h to make the SiO2 particles stably adhere, thereby obtaining a scale structure coating based on a PDMS / Co@SiO2 composite material.

[0017] Preferably, the coating operation is selected from spraying, dipping or dripping.

[0018] Preferably, the particle size of the SiO2 nanoparticles is 50-100nm.

[0019] The second object of the present application is to provide a scale structure coating based on a PDMS / Co@SiO2 composite material prepared by the above preparation method.

[0020] Preferably, the scale structure coating based on the PDMS / Co@SiO2 composite material is periodically arranged rectangular scale structure, the scales are tilted and raised in one direction, the surface is rough, and a micro-nano composite structure is formed.

[0021] Preferably, the thickness of the scale structure coating based on the PDMS / Co@SiO2 composite material is 100-300 mu m.

[0022] More preferably, the thickness of the scale structure coating based on the PDMS / Co@SiO2 composite material is 200-300 mu m; the thickness range can ensure that the scale structure has good support and elasticity, and can avoid collapse or excessive tilting. The scale structure is suitable for the doctor blade coating process, is easy to demold, has good structural integrity, and is not easy to curl or crack. The scale structure can be repeatedly tilted or reset, and meets the design goal of'repeatable driving'. When the thickness of the scale structure coating based on the PDMS / Co@SiO2 composite material is less than 100 mu m, the scale structure has insufficient tilting capacity and the mechanical support force is reduced, and even the mold texture with the scale structure cannot be completely replicated. When the thickness of the scale structure coating based on the PDMS / Co@SiO2 composite material is more than 300 mu m, the scale structure coating based on the PDMS / Co@SiO2 composite material is too heavy, the magnetic response sensitivity is reduced, and the structural flexibility is insufficient.

[0023] The third object of the present application is to provide the application of the scale structure coating based on the PDMS / Co@SiO2 composite material in the preparation of ice-proof or deicing materials.

[0024] Compared with the prior art, the present application has the following beneficial effects: 0、The present application provides a preparation method of a scale structure coating based on a PDMS / Co@SiO2 composite material. Vinyl-terminated polydimethylsiloxane is used as a matrix, and methyl hydrogen siloxane is used as a curing agent. The matrix and the curing agent are mixed to obtain a prepolymer solution. The cobalt powder is dispersed in the prepolymer solution, and after degassing, a PDMS / Co mixture is obtained. The PDMS / Co mixture is coated on the surface of a mold with a scale structure, and the mold is stripped after curing treatment. During the curing process, the vinyl group of polydimethylsiloxane and the Si-H bond of methyl hydrogen siloxane undergo addition reaction to form a cross-linked three-dimensional network. At the same time, the cobalt powder particles are embedded in the cross-linked three-dimensional network to form a composite structure, and a PDMS / Co scale array is obtained. The surface of the PDMS / Co scale array is modified with SiO2 nanoparticles to obtain a scale structure coating based on a PDMS / Co@SiO2 composite material.

[0025] The micrometer-sized Co and the PDMS / Co scale array provide a strong structural framework, which endows the scale structure coating based on the PDMS / Co@SiO2 composite material with excellent magnetic response and photothermal performance; the SiO2 nanoparticle modification further enhances the surface roughness and hydrophobicity of the scale structure coating based on the PDMS / Co@SiO2 composite material, and greatly reduces the actual contact area of the liquid droplet with the surface of the scale structure coating based on the PDMS / Co@SiO2 composite material by forming a stable air cushion layer. In addition, under the action of an external magnetic field, the scale structure coating based on the PDMS / Co@SiO2 composite material realizes the efficient directional transport of liquid droplets through the "magnetic imbalance-elastic rebound" mechanism. This mechanism not only breaks the initial static equilibrium of the liquid droplets, but also pushes the liquid droplets to move along the predetermined path through the elastic rebound of the scales, significantly improving the transport efficiency of the liquid droplets.

[0026] 2, The scale structure coating based on the PDMS / Co@SiO2 composite material prepared by the application not only provides a new anti-icing coating solution, but also innovatively exhibits a technical integration idea, i.e., the synergistic effect of the magnetic response mechanism and the photothermal effect. This dual mechanism endows the scale structure coating based on the PDMS / Co@SiO2 composite material with excellent anti-icing performance in low-temperature and high-humidity extreme environments, and also enables precise control of liquid droplets through magnetic force. Compared with the traditional anti-icing materials which rely on a single physical or chemical action mechanism, the application successfully breaks through the limitations of traditional anti-icing technology by integrating cross-disciplinary technologies, providing a new idea for the design and development of intelligent responsive functional materials.

[0027] 3, The scale structure coating based on the PDMS / Co@SiO2 composite material of the application combines the dual mechanisms of magnetic response and photothermal anti-icing, realizing the synergistic optimization of efficient directional transport of liquid droplets and long-term anti-icing performance. At the same time, the scale structure coating based on the PDMS / Co@SiO2 composite material exhibits excellent anti-icing performance at-15℃ low temperature environment, effectively inhibiting water droplet icing, and under simulated sunlight irradiation, the surface of the scale structure coating based on the PDMS / Co@SiO2 composite material can reach 52.1℃, which is significantly better than traditional anti-icing materials.

[0028] 4, In terms of directional transport of liquid droplets, the application successfully realizes efficient directional transport of liquid droplets by controlling the strength and direction of the magnetic field. The synergistic effect of the superhydrophobic structure on the surface of the scale structure coating based on the PDMS / Co@SiO2 composite material and the magnetic responsive scale not only effectively reduces the frictional resistance of the liquid droplets, but also ensures the precise transport of the liquid droplets through the "magnetic imbalance-elastic rebound" mechanism. This feature provides a new idea for the application of microfluidic systems and opens up a new path for future intelligent liquid droplet manipulation technology. BRIEF DESCRIPTION OF DRAWINGS

[0029] Figure 1 The preparation process of the PCS of the present application is shown in the figure.

[0030] Figure 2 The macrostructure, micro-morphology, element composition and wetting performance of the PCS of Example 1 are shown in the figure; wherein, a is the external shape of the PCS, b is the side view of the PCS, c is the top view of the PCS, d is the SEM image of the PCS, e is the local enlarged view of the d image, f is the element distribution image corresponding to the e image, g is the wetting effect image of the water droplet on the surface of the PCS in the natural state, h is the wetting effect image of the water droplet on the surface of the PCS under the action of the magnetic field, and i is the mechanism diagram of the super-hydrophobicity of the surface of the PCS.

[0031] Figure 3 The water droplet transportability of the PCS of Example 1 under the external magnetic field is shown in the figure; wherein, a is the schematic diagram of the magnet moving towards the WS direction, b is the diagram of the PCS moving under the magnet moving towards the WS direction, the moving speeds are 5 cm / s, 7 cm / s and 9 cm / s respectively, c is the relationship diagram between the moving distance of the water droplet on the PCS and the moving speed of the magnet in the WS direction, d is the schematic diagram of the magnet moving towards the AS direction, e is the diagram of the PCS moving under the magnet moving towards the AS direction, the moving speeds are 5 cm / s, 7 cm / s and 9 cm / s respectively, and f is the relationship diagram between the moving distance of the water droplet on the PCS and the moving speed of the magnet in the AS direction.

[0032] Figure 4 The force analysis diagram of the water droplet transport on the surface of the PCS of Example 1 is shown in the figure; wherein, a is the continuous movement process of the water droplet when the magnet moves along the WS direction; b is the schematic diagram of the magnetic imbalance stage and the corresponding force analysis in the a diagram; and c is the schematic diagram of the elastic rebound stage and the corresponding force analysis diagram in the a diagram.

[0033] Figure 5 The force analysis diagram of the water droplet transport on the surface of the PCS of Example 1 is shown in the figure; wherein, a is the continuous movement process of the water droplet when the magnet moves along the WS direction; b is the schematic diagram of the magnetic imbalance stage and the corresponding force analysis in the a diagram; and c is the schematic diagram of the elastic rebound stage and the corresponding force analysis diagram in the a diagram.

[0034] Figure 6 The anti-icing performance analysis diagram of the PCS of Example 1 is shown in the figure; wherein, a is the experimental device diagram, b is the infrared thermal imaging diagram of the PCS and the PS, c is the ice formation diagram on the surfaces of the PCS and the PS before and after the xenon lamp irradiation, c1 is before the irradiation, c2 is after the irradiation, d is the ice formation schematic diagram of the surfaces of the PCS and the PS and the light-heat enhancement mechanism diagram of the surface of the PCS, e is the average temperature change of the surfaces of the PCS and the PS under 1 sunlight, f is the temperature-time diagram of the water droplet ice formation process, and g is the ice formation time.

[0035] Figure 7 Figure 8 is a PCS deicing performance analysis diagram of Example 1; a is a diagram of ice droplet melting on the surface of the PCS before and after xenon lamp irradiation, a1 is before irradiation, a2 is after irradiation, b is a diagram of ice melting on the surface of the PCS, and c is a diagram of the contact angle and morphology of the surface of the PCS after 10 times of photothermal deicing. DETAILED DESCRIPTION

[0036] The technical solutions of the present application will be described clearly and completely below in combination with the data in the embodiments of the present application. Obviously, the described embodiments are only some of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application.

[0037] It should be noted that the professional terms used in the present application are only for the purpose of describing the specific embodiments and are not intended to limit the scope of protection of the present application. Unless otherwise specified, the various raw materials, reagents, instruments and equipment used in the following embodiments of the present application can be purchased from the market or prepared by the existing method. Among them, the vinyl-terminated polydimethylsiloxane is purchased from Sigma Aldrich, which is denoted as PDMS.

[0038] In the prior art, although the traditional anti-icing materials can play a role, due to the problems of low energy efficiency and poor environmental adaptability, they cannot effectively meet the demand of modern technology for high-performance materials.

[0039] In view of the deficiencies of the prior art, the present application provides a scale structure coating based on PDMS / Co@SiO2 composite material, a preparation method and application. The present application constructs a unique multi-level micro-nano structure by compounding cobalt powder with polydimethylsiloxane and modifying the surface with silicon dioxide. Among them, the PDMS / Co scale array formed by the micron-sized Co powder and the prepolymer liquid provides a solid structural framework, which endows the scale structure coating based on PDMS / Co@SiO2 composite material with excellent magnetic responsiveness and photothermal performance; the SiO2 nano-based scale structure coating based on PDMS / Co@SiO2 composite material further enhances the surface roughness and hydrophobicity, and by forming a stable air cushion layer, the actual contact area of the liquid droplet with the surface of the scale structure coating based on PDMS / Co@SiO2 composite material is greatly reduced. Under the action of an external magnetic field, the scale structure coating based on PDMS / Co@SiO2 composite material realizes the efficient directional transport of liquid droplets through the "magnetic imbalance-elastic rebound" mechanism. This mechanism not only breaks the initial static equilibrium of the liquid droplets, but also pushes the liquid droplets to move quickly along the predetermined path through the elastic rebound of the scales, significantly improving the transport efficiency of the liquid droplets.

[0040] In order for those skilled in the art to more clearly understand the technical solutions of the present application, the following will be described in detail in conjunction with specific embodiments: The mold with a scale structure in Embodiments 1-6 of the present application is prepared according to the following steps: The polished PVC substrate is fixed on a steel operating table inclined at 45°, a tungsten steel blade is installed on a three-axis transmission device, the cutting path is controlled by G code programming to ensure the consistency of the scale structure; the blade cuts from bottom to top along the Y axis (feed speed 2 mm / s, spindle speed 3000 rpm) to form a regular scale structure; in order to reduce the demolding resistance of the cured PDMS, two-stage surface treatment is performed after cutting: oxygen plasma cleaning (Harrick Plasma, 18W / 120s) to remove cutting residues and activate the surface; vapor deposition of 0.5% fluorosilane to build a low surface energy layer and improve the demolding effect; after the mold cutting is completed, it is subjected to oxygen plasma cleaning to further improve the surface energy, ensure the formation of a good interface between the PDMS and the mold, and obtain a mold with a scale structure, the length of the mold is 20 mm, and the depth is 3 mm.

[0041] Embodiment 1 A preparation method of a scale structure coating based on a PDMS / Co@SiO2 composite material, comprising the following steps: S1, weigh PDMS and methyl hydrogen siloxane in a mass ratio of 10:1 and transfer to a 50 mL glass beaker, use a magnetic stirrer to stir at a speed of 500 rpm for 5 min until the mixed system presents a uniform milky white color to obtain a prepolymer liquid.

[0042] S2, add 0.2 g of cobalt powder to 1 g of prepolymer liquid gradually, and at the same time, increase the stirring speed to 800 rpm, continue to stir for 15 min to ensure uniform dispersion of the cobalt powder and form a uniform system; then move to a vacuum drying dish, and treat at -30 kPa and 25℃ for 10 min until no continuous bubbles escape; after the degassing is completed, take out and stand for 5 min to obtain a PDMS / Co mixture.

[0043] S3, horizontally fix the mold with a scale structure on a clean workbench, use a glass rod to coat the PDMS / Co mixture on the surface of the mold with a scale structure at a speed of 2 cm / s and an inclination angle of 45° by using a scraping method, ensure that the PDMS / Co mixture completely covers the micro-nano structure layer of the mold, then transfer the coated mold to a vacuum drying dish, and treat at -30 kPa and 25℃ for 15 min to make the PDMS / Co mixture completely fill the micron-level gap; then move the mold into a vacuum drying oven and heat at 80℃ for 2 h, take out and naturally cool to 40℃, and peel off the mold with a scale structure to obtain a PDMS / Co scale array.

[0044] S4, 0.1 g of SiO2 nanoparticles was dispersed in 10 mL of anhydrous ethanol, and after ultrasonic treatment for 30 min, a suspension was obtained; the suspension was sprayed on the surface of the PDMS / Co flake array, and cured at 60℃ for 2 h to obtain a flake structure coating based on PDMS / Co@SiO2 composite material, abbreviated as PCS.

[0045] Example 2 A preparation method of a flake structure coating based on PDMS / Co@SiO2 composite material, which is the same as the preparation method of Example 1, except that the mass ratio of PDMS to methyl hydrogen siloxane in S1 is replaced by 8:1, to obtain a flake structure coating based on PDMS / Co@SiO2 composite material.

[0046] Example 3 A preparation method of a flake structure coating based on PDMS / Co@SiO2 composite material, which is the same as the preparation method of Example 1, except that the mass ratio of PDMS to methyl hydrogen siloxane in S1 is replaced by 12:1, to obtain a flake structure coating based on PDMS / Co@SiO2 composite material.

[0047] Example 4 A preparation method of a flake structure coating based on PDMS / Co@SiO2 composite material, which is the same as the preparation method of Example 1, except that the amount of cobalt powder in S2 is replaced by 0.3 g, to obtain a flake structure coating based on PDMS / Co@SiO2 composite material.

[0048] Example 5 A preparation method of a flake structure coating based on PDMS / Co@SiO2 composite material, which is the same as the preparation method of Example 1, except that the curing conditions in S3 are replaced by "constant temperature curing at 100℃ for 1h", to obtain a flake structure coating based on PDMS / Co@SiO2 composite material.

[0049] Example 6 A preparation method of a flake structure coating based on PDMS / Co@SiO2 composite material, which is the same as the preparation method of Example 1, except that the curing conditions in S3 are replaced by "constant temperature curing at 60℃ for 3h", to obtain a flake structure coating based on PDMS / Co@SiO2 composite material.

[0050] Observation Figure 2 It can be seen from the a figure in that the PCS as a whole is in the shape of a rectangular strip, and the surface is regularly arranged with longitudinal flake structures.Figure 2 Figure b shows that PCS presents a continuous flake structure. This ordered arrangement provides a stable geometric path for the directional transport of droplets, while giving the flake structure coating based on PDMS / Co@SiO2 composite material surface anisotropy. Figure 2 Figure c shows that the scales are evenly and continuously distributed on the substrate, indicating that the preparation process provided by the present invention has good repeatability and structural consistency.

[0051] Figure 2 Figures d, e, and f reveal that the surface of the PDMS / Co@SiO2 composite-based flake-structured coating possesses a multi-level micro-nanostructure, characterized by microscale undulations and a large distribution of nanoparticles. The abundant pores and gaps between the nanoparticles trap air upon contact with liquid droplets, forming a stable air cushion and effectively reducing the adhesion between the droplets and the PDMS / Co@SiO2 composite-based flake-structured coating. This structural feature plays a key role in establishing superhydrophobic properties and also creates conditions for low-resistance transport of droplets. Figure 2 Figure f further demonstrates the uniformity of the surface composition of the PDMS / Co@SiO2 composite-based flake coating. The elements C, O, Si, and Co are evenly distributed across the PCS flake surface, indicating good dispersion of the Co nanoparticles within the PDMS matrix. Furthermore, SiO2 nanoparticles are uniformly deposited on the surface of the PDMS / Co@SiO2 composite-based flake coating. This uniform compositional distribution is essential for achieving uniform photothermal conversion and stable magnetic response behavior, and also helps maintain consistency in the thermal and mechanical fields at the local scale.

[0052] Depend on Figure 2 Figure g shows that in the natural state, the PCS surface exhibits a typical Cassie-Baxter state, with a water droplet contact angle (CA) of up to 162°±3° and a rolling angle (SA) of less than 5°, indicating that the PCS surface has excellent superhydrophobic properties. After applying a magnetic field (see 2h in the figure), the scales elastically bend under the action of the magnetic field to form a three-level structure similar to a step. Although the local geometric deformation causes a pinning effect on the contact line, the apparent contact angle of the water droplet remains at 158°±2°, indicating that PCS can still maintain a high degree of hydrophobicity under dynamic magnetic response. This stable superhydrophobic state is mainly attributed to the double rough structure constructed by the SiO2 nanoparticles modified on the PCS surface. The gaps between the particles can effectively capture air to form an air cushion, thereby significantly reducing the solid-liquid contact area (such as Figure 2 This not only helps to enhance the anti-icing performance, but also plays an important role in promoting the rapid sliding and low retention behavior of droplets on the surface.

[0053] like Figure 3As shown, the scales have an inclination angle of 45°. The direction along the scales is defined as the forward inclination direction, abbreviated as WS, and the direction against the scales is defined as the reverse inclination direction, abbreviated as AS. The initial position of the magnet is set to 10 mm from the droplet level. When the magnet moves along the WS direction (see Figure 3 (As shown in Figures b and c in the figure), it was found that the faster the magnet speed, the shorter the droplet start time, and the higher the droplet transport efficiency. Specifically, when the magnet moved at a speed of 9 cm / s, the droplet began to move at 0.11 seconds, moved 1.84 mm at 0.2 seconds, and had moved 6.85 mm at 0.3 seconds. When the magnet speed was reduced to 7 cm / s, the droplet began to move at 0.14 seconds, moved 0.52 mm at 0.2 seconds, and moved 4.4 mm at 0.3 seconds. When the magnet speed was further reduced to 5 cm / s, the droplet began to move at 0.2 seconds, and moved only 2.36 mm at 0.3 seconds.

[0054] In summary, the speed of the magnet significantly affects the droplet's launch time and travel distance. The faster the magnet speed, the shorter the droplet launch time and the faster the droplet's travel speed, indicating that the launch of the droplet under the action of the magnetic force is closely related to the speed of the magnet movement. However, the final transport distance of the droplet does not vary much at different speeds, indicating that within a specific speed range, the droplet transport efficiency is limited by the synergistic effect of the magnetic field force, the deformation response of the scale structure, and the surface properties.

[0055] A. Magnetic response effect in the reverse tilt direction (AS): The motion behavior of the droplet when the magnet moves along the AS direction, as shown in Figures d~e. Compared with the downwind direction (WS), the droplet's motion distance is shorter at the same magnet speed. Specifically, when the magnet moves at a speed of 9 cm / s, the droplet starts to move at 0.11 s, and the motion distance is 1.3 mm at 0.2 s and 6.2 mm at 0.3 s. In the AS direction under the same conditions, the droplet's motion distance is significantly smaller in the upwind direction than in the downwind direction, with a difference of about 0.7 mm (Ad=0.7±0.1). When the magnet speed is 7 cm / s, the droplet starts to move at 0.14 s, and the motion distance is 0.33 mm at 0.2 s and 3.4 mm at 0.3 s; when the magnet speed is reduced to 5 cm / s, the droplet starts to move at 0.2 s, and the motion distance is 2.3 mm at 0.3 s. This phenomenon shows that the direction of the magnetic force has a significant impact on the motion of the droplet. Although the speed of the magnet still has a significant impact on the start-up time and transport distance of the droplet, in the upwind direction, the droplet's motion distance is shorter, mainly due to the difference in the droplet's deformation response in different driving directions caused by the magnetic field gradient and the anisotropy of the PCS scale structure. The direction dependence of the magnetic field distribution and the difference in the geometric deformation ability of PCS in the WS and AS directions are the main reasons for the directionality of the droplet motion efficiency.

[0056] The magnet moving speed has a significant impact on the start-up time and transport efficiency of the droplet. Higher magnet speed not only accelerates the start-up of the droplet, but also effectively improves the motion speed of the droplet, but within a certain range, the motion distance of the droplet changes relatively small, which shows that the synergy of magnetic force and scale structure coating structure based on PDMS / Co@SiO2 composite material plays a key role. In different magnet moving directions, the transport distance of the droplet shows direction dependence, which is mainly related to the structural characteristics of the scale structure coating based on PDMS / Co@SiO2 composite material. The multi-level micro-nano structure on the surface of the scale structure coating based on PDMS / Co@SiO2 composite material will induce different magnetic response effects in different directions, thereby affecting the motion trajectory and transport efficiency of the droplet. This finding provides valuable reference for the future design of magnetic response scale structure coating based on PDMS / Co@SiO2 composite material, and also provides new ideas for how to optimize the droplet directional transport system.

[0057] In summary, by adjusting the moving speed and direction of the magnet, efficient directional transport of the droplet can be achieved, which is of great significance for the application of microfluidic technology and aircraft ice prevention. Especially in the extreme climate application scenario of aircraft ice prevention, this ability to precisely control the motion of the droplet has important value.

[0058] In order to further understand the mechanism of the droplet's directional transport on the PCS, Figure 4The synergy of the magnet, the scale, and the water droplet in the directional transport of the water droplet is demonstrated. Figure 4 FIG. a in the above shows the specific motion process of the water droplet when the magnet moves in the WS direction. Figure 4 FIGS. b and c in the above show the force analysis of the water droplet motion. When the magnet moves along the direction of the scale, the scale undergoes elastic bending deformation under the influence of the magnetic field. Specifically, when the magnet is located below the scale, the scale undergoes controllable bending deformation under the action of the magnetic field gradient force, and an inclined step structure is generated. This bending deformation of the scale causes the water droplet to roll off the surface of the scale, and the motion direction of the water droplet is closely related to the interaction between the structure of the scale and the magnetic field. When the magnet moves directly above the magnetic field, the scale becomes a planar step; when the magnet moves to the rear, the bending form of the scale re-forms an inclined step structure. Overall, this structure presents an inverted trapezoidal geometry, providing a stable trajectory for the motion of the water droplet.

[0059] Figure 4 FIGS. b and c in the above show two key processes of the scale-shaped transport of the water droplet driven by the magnet - the magnetic imbalance period and the elastic rebound period.

[0060] Magnetic imbalance period: When the magnet moves in the WS direction (along the direction of the inclination of the scale), the influence of the magnetic field gradient force on the scale causes the scale to bend, breaking the initial static equilibrium of the water droplet. The water droplet begins to move in the WS direction due to the combined action of the magnetic field driving and the deformation of the scale. At this stage, the resultant force (FR) of the water droplet can be represented by the following formula:

[0061] .

[0062] where G is the gravity of the water droplet, f is the friction between the water droplet and the scale, and a is the inclination angle of the scale. In this stage, the motion trend of the water droplet is mainly formed by the combined action of these resultant forces, and after the initial static equilibrium of the water droplet is broken, the water droplet begins to roll directionally along the surface of the scale.

[0063] Elastic rebound period: When the magnet quickly moves out of the range of action, the scale quickly rebounds to the original state without the magnetic force. At this time, the water droplet continues to move quickly along the predetermined path under the push of the elastic rebound force of the scale due to the loss of the support of the magnetic field. The motion trend of the water droplet is driven by the following resultant force:

[0064] .

[0065] In the elastic rebound period, the elastic restoring force of the scale provides a directional thrust, enabling the water droplet to continue moving in the WS direction, ensuring the efficiency of the directional transport of the water droplet.

[0066] Figure 5Figure a shows the specific motion process of the water droplet when the magnet moves in the AS direction. When the magnet moves in the AS direction (against the tilt of the scale), the motion of the droplet is still affected by the similar magnetic imbalance period and elastic rebound period. Although the directions are opposite, the motion of the droplet is still determined by the influence of the magnetic field on the scale and the elastic deformation of the scale. Figure 5 Figure b shows that when the magnet moves in the AS direction, the magnetic imbalance will change the static balance of the droplet, pushing the droplet to move in the AS direction. The motion trend of the droplet can be expressed by the resultant force:

[0067] .

[0068] After the magnet quickly moves out of the range of action, Figure 5 In Figure c, the droplet is affected by the rebound force of the scale and moves along the tilt direction of the scale (WS).

[0069] .

[0070] In general, the transport distance and efficiency of droplets in the AS direction are different from those in the WS direction, but are also controlled by both the magnetic field and the scale deformation response.

[0071] The core mechanism of this process lies in the dual effects of magnetic imbalance and elastic rebound, which not only affect the efficiency of droplet initiation and directional transport, but also provide new insights into the design of magnetically responsive flake-structured coatings based on PDMS / Co@SiO2 composite materials. By precisely controlling the direction and speed of the magnet's movement, the present invention can efficiently manipulate the droplet's path, a feature that has broad application prospects in anti-icing technology and microfluidic systems. Especially in low-temperature environments, the rapid and directional transport of droplets can effectively prevent their accumulation and ice formation, significantly improving the anti-icing performance of PCS.

[0072] The photothermal effect plays a crucial role in the anti-icing properties of materials, particularly in low-temperature environments. Photothermally responsive materials absorb solar energy and convert it into heat, effectively inhibiting the freezing of water droplets. This study experimentally evaluated the photothermal responsiveness of a flake-structured coating based on a PDMS / Co@SiO2 composite material. The photothermal conversion efficiency was further analyzed based on the temperature rise observed under simulated sunlight.

[0073] In order to evaluate the photothermal conversion capability of the flake structure coating based on PDMS / Co@SiO2 composite material, the present invention uses a xenon lamp system simulating solar energy, such as Figure 6 As shown in Figure a, the simulation is 100mW / cm 2temperature of the PCS under light conditions. The initial temperature of the PCS was 20℃, and the temperature rise of the PCS surface under light conditions was continuously recorded by the infrared thermal imager. The key was to observe the temperature rise rate of the PCS within a certain time and its final temperature stability, which revealed the response ability of the PCS to light and its thermal energy conversion efficiency. The infrared thermal images of PCS and PS are shown in FIG. b of Figure 6

[0074] According to FIG. b, Figure 6 The PCS based on PDMS / Co@SiO2 composite material showed significant photothermal conversion ability under light conditions. Under 100 mW / cm 2 of solar irradiation, the surface temperature of the PCS rapidly rose to 72.1℃, which was significantly higher than the 34.3℃ of the conventional material. The temperature rise of the PCS was 52.1℃, which was much higher than the 14.3℃ of the conventional material, and the advantage was obvious. This result showed that the addition of Co nanoparticles greatly improved the photothermal conversion efficiency of the PCS based on PDMS / Co@SiO2 composite material. The wide spectral absorption characteristics of Co enabled it to effectively absorb light energy from the ultraviolet to the near-infrared band and convert it into heat energy. Co nanoparticles on the surface of the PCS could effectively convert the absorbed light energy into heat energy, thereby promoting the rise in the surface temperature of the water droplets and delaying the icing process.

[0075] The application of photothermal responsive materials is not only limited to improving the anti-icing performance of materials, but more importantly, it provides an innovative solution to cope with extreme weather conditions. The excellent photothermal properties of the PCS enable it to self-heat through solar energy in low-temperature environments, thereby maintaining an anti-icing state. This feature is particularly suitable for the aviation and power equipment fields, where materials need to maintain high performance under extreme weather conditions.

[0076] Through the photothermal effect, the PCS based on PDMS / Co@SiO2 composite material can increase the surface temperature by absorbing natural light (such as sunlight) without external power supply, thereby effectively avoiding the icing phenomenon. Compared with traditional electric heating anti-icing technology, the advantage of photothermal anti-icing materials lies in their low energy consumption and environmental friendliness. The PCS does not require additional power support and can utilize solar energy for energy conversion, which not only reduces energy consumption but also reduces environmental burden.

[0077] B. Anti- / de-icing performance: ​Anti-icing performance is one of the most important functions of the flake structure coating based on the PDMS / Co@SiO2 composite material in the present invention. Especially in low-temperature environments, the anti-icing effect of the flake structure coating based on the PDMS / Co@SiO2 composite material directly affects the feasibility and reliability of its application field. In traditional anti-icing technologies, electric heating, mechanical deicing or chemical deicing methods are usually relied on. Although these methods are effective, they have problems of high energy consumption, environmental pollution and difficult maintenance. In contrast, the anti-icing technology of the synergistic effect of photothermal and superhydrophobicity proposed in the present invention not only has excellent anti-icing effect in low-temperature environments, but also can effectively reduce energy consumption, and has higher environmental protection and sustainability.

[0078] In order to comprehensively evaluate the anti-icing performance of the PDMS / Co@SiO2 composite flake structure coating, the present invention conducted a water droplet freezing experiment at a low temperature of -15°C. A 10μL water droplet was placed on the surface of different PDMS / Co@SiO2 composite flake structure coatings, and the freezing process of the water droplet on the surface of the PDMS / Co@SiO2 composite flake structure coating was observed. Figure 6 Figure c and Figure 7 As shown in Figure a, the humidity was maintained at approximately 50%, simulating the humidity conditions found in a real environment. To further verify the anti-icing effectiveness of the PDMS / Co@SiO2 composite flake-structured coating, the present invention also conducted tests in the presence and absence of sunlight, monitoring the freezing process of water droplets using a high-precision thermo-hygrometer and an infrared thermal imager.

[0079] Depend on Figure 6 It was concluded from c that the flake structure coating based on PDMS / Co@SiO2 composite material showed a significant anti-icing effect in a low temperature environment of -15°C. Compared with traditional coatings, the flake structure coating based on PDMS / Co@SiO2 composite material showed excellent anti-icing performance under both light and no light conditions. Under no light conditions, the freezing time of water droplets on the surface of the flake structure coating based on PDMS / Co@SiO2 composite material was longer, which delayed the freezing process. Specifically, under the same environment, the freezing time of water droplets on the PCS surface was nearly doubled that of traditional coatings, and the droplets remained liquid on the PCS surface for a longer time without freezing.

[0080] When light illumination is applied, the anti-icing performance of PCS is further enhanced. Figure 6The results in Figure c show that under simulated sunlight, the PCS significantly increases the surface temperature within a short period of time, almost completely preventing water droplets from freezing. Under sunlight, the water droplets on the PCS surface show no signs of frost or ice formation and continue to evaporate without accumulating. This phenomenon demonstrates that the photothermal effect of the PDMS / Co@SiO2 composite flake-structured coating plays a significant role in the anti-icing process, effectively preventing water droplets from freezing by absorbing sunlight and raising the surface temperature.

[0081] The excellent anti-icing performance of the coating demonstrates the great potential of the synergistic effects of photothermal and superhydrophobicity in low-temperature environments. First, the flake structure coating based on the PDMS / Co@SiO2 composite material reduces the contact area between the water droplets and the surface through the superhydrophobic structure, thereby delaying the formation of ice nuclei. On the surface of the flake structure coating based on the PDMS / Co@SiO2 composite material, the water droplets hardly come into contact with the surface and stay at the tip of the scales to form an air cushion layer, which effectively reduces the possibility of ice formation. Secondly, the introduction of the photothermal effect enables PCS to self-heat by absorbing sunlight. Even in extremely low-temperature environments, the flake structure coating based on the PDMS / Co@SiO2 composite material can still maintain a high surface temperature, further enhancing the anti-icing effect.

[0082] like Figure 7 As shown in Figure a, in the dark, it takes 58 seconds for the ice droplet on the PCS surface to completely melt; in the light, the process takes only 32 seconds, a 44.8% reduction in melting time. This efficient de-icing process is due to the cobalt powder's excellent light absorption and efficient photothermal conversion properties, which can generate a localized heat source, thereby accelerating the ice-water phase transition. Figure 7 Figure b shows the dynamic evolution of ice melting, indicating that the melting of ice starts at the bottom and gradually advances upward until it is completely liquefied. This directional melting behavior is driven by the vertical temperature gradient caused by local bottom heating. This mechanism helps to avoid the formation of strongly adhered ice layers, thereby achieving more efficient and low-energy deicing operations. Figure 7 As shown in Figure c, PCS exhibits excellent superhydrophobic properties after 10 cycles of icing and deicing, with its water contact angle only slightly decreasing from 162°±3° to 158°±2°. This result fully demonstrates the mechanical and chemical stability of PCS under repeated thermal and hygroscopic stresses. This excellent durability makes PCS a promising candidate for long-term anti-icing and de-icing applications in harsh environments.

[0083] The combination of photothermal and superhydrophobic properties not only improves the anti-icing ability of PCS, but also provides a high-energy-efficient and environmentally friendly solution. Compared with traditional electric heating anti-icing methods, photothermal anti-icing materials have significant advantages, especially in situations where electricity cannot be used or access to power is not available. Photothermal anti-icing materials can self-heat through natural light, avoiding the high energy consumption and environmental pollution problems of traditional heating methods.

[0084] In addition, this technology also has good application prospects, especially in the fields of aviation and energy. In the field of aviation, the problem of ice prevention on the surface of aircraft landing gear and wings has long plagued aviation safety. The use of photothermal anti-icing technology such as PCS can effectively solve this problem, especially in low temperature and high humidity environments. In addition, power equipment such as high-voltage transmission lines and wind turbines also face serious icing problems, and PCS can provide a low-energy, efficient and environmentally friendly anti-icing solution.

[0085] It should be noted that when numerical ranges are involved in the present application, it is understood that each numerical range is intended to include every number between the two endpoints, as well as any one of the endpoints. Since the same steps and examples are used, the preferred embodiments are described to prevent redundancy. Although the preferred embodiments of the present application have been described, those skilled in the art, once aware of the basic inventive concept, can make additional changes and modifications to these embodiments. Therefore, the appended claims are intended to include the preferred embodiments and all changes and modifications falling within the scope of the present application.

Claims

1. A method for preparing a flake structure coating based on a PDMS / Co@SiO2 composite material, characterized in that: The following steps are involved: Using vinyl-terminated polydimethylsiloxane as a matrix and methyl hydrogensiloxane as a curing agent, the matrix and the curing agent are mixed to obtain a prepolymer solution; Dispersing cobalt powder in the prepolymer solution and degassing to obtain a PDMS / Co mixture; The PDMS / Co mixture is coated on the surface of a mold with a scale structure. After curing, the mold is peeled off. During the curing process, the vinyl groups of polydimethylsiloxane react with the Si-H bonds of methylhydrogensiloxane to form a cross-linked three-dimensional network. At the same time, cobalt powder particles are embedded in the cross-linked three-dimensional network to form a composite structure, resulting in a PDMS / Co scale array. SiO2 nanoparticles were modified on the surface of PDMS / Co flake array to obtain a flake structure coating based on PDMS / Co@SiO2 composite material.

2. The method for preparing a flake structure coating based on a PDMS / Co@SiO2 composite material according to claim 1, characterized in that: The mass ratio of vinyl terminated polydimethylsiloxane to methyl hydrogensiloxane is 8-12:

1.

3. The method for preparing a flake structure coating based on a PDMS / Co@SiO2 composite material according to claim 1, characterized in that: The mass ratio of cobalt powder to prepolymer solution is 0.2~0.3:

1.

4. The method for preparing a flake structure coating based on a PDMS / Co@SiO2 composite material according to claim 1, characterized in that: The curing treatment conditions are: standing at 60℃~100℃ for 1h~3h.

5. The method for preparing a flake structure coating based on a PDMS / Co@SiO2 composite material according to claim 1, characterized in that: The particle size of SiO2 nanoparticles is 50nm~100nm.

6. The method for preparing a flake structure coating based on a PDMS / Co@SiO2 composite material according to claim 1, characterized in that: SiO2 nanoparticles are modified on the surface of PDMS / Co flake arrays by solution method or vapor deposition method.

7. A flake structure coating based on PDMS / Co@SiO2 composite material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 6.

8. The PDMS / Co@SiO2 composite material-based flake structure coating according to claim 7, characterized in that: The flake structure coating based on PDMS / Co@SiO2 composite material is a periodically arranged flaky flake structure. The scales are tilted and warped in one direction, with a rough surface and a micro-nano composite structure.

9. The PDMS / Co@SiO2 composite material-based flake structure coating according to claim 7, characterized in that: The thickness of the flake structure coating based on PDMS / Co@SiO2 composite material is 100μm~300μm.

10. Use of the PDMS / Co@SiO2 composite material-based flake structure coating according to claim 7 in the preparation of anti-icing or deicing materials.

Citation Information

Cited By

  • Photo-thermal polymer / waste carbon composite material as well as spray preparation method and application thereof

    CN121574653A

  • Magnetic response muscle bionic anti-icing substrate and preparation method thereof

    CN121851993A